Direct analysis of pollen fitness by flow cytometry: implications for pollen response to stress. (18th March 2019) - Luria, Gilad; Rutley, Nicholas; Lazar, Itay; Harper, Jeffery F.; Miller, Gad
Summary : Sexual reproduction in flowering plants depends on the fitness of the male gametophyte during fertilization. Because pollen development is highly sensitive to hot and cold temperature extremes, reliable methods to evaluate pollen viability are important for research into improving reproductive heat stress (HS) tolerance. Here, we describe an approach to rapidly evaluate pollen viability using a reactive oxygen species (ROS) probe dichlorodihydrofluorescein diacetate (i.e. H2 DCFDA‐staining) coupled with flow cytometry. In using flow cytometry to analyze mature pollen harvested from Arabidopsis and tomato flowers, we discovered that pollen distributed bimodally into 'low‐ROS' and 'high‐ROS' subpopulations. Pollen germination assays following fluorescence‐activated cell sorting revealed that the high‐ROS pollen germinated with a frequency that was 35‐fold higher than the low‐ROS pollen, supporting a model in which a significant fraction of a flower's pollen remains in a low metabolic or dormant state even after hydration. The ability to use flow cytometry to quantify ROS dynamics within a large pollen population was shown by dose‐dependent alterations in DCF‐fluorescence in response to oxidative stress or antioxidant treatments. HS treatments (35°C) increased ROS levels, which correlated with a 60% reduction in pollen germination. These results demonstrate the potential of using flow cytometry‐based approaches to investigate metabolic changes during stress responses in pollen. Significance Statement: Using H2 DCFDA‐staining coupled with a flow cytometry approach, we demonstrate the ability to score pollen viability on the population scale. Applying this method to Arabidopsis and tomato pollen, we discovered that pollen distributes bimodally into a dormant/inactive 'low‐ROS' and metabolically active 'high‐ROS' subpopulations. In addition, we used this approach to measure dynamic changes in pollen ROS homeostasis in response to abiotic stresses. These examples only scratch the surface of the potential of using flow cytometry for studying pollen metabolism, pollen physiology and many other applications.